1985
DOI: 10.1002/tea.3660220208
|View full text |Cite
|
Sign up to set email alerts
|

Development of an integrated process skill test: TIPS II

Abstract: The purpose of this project was to develop a valid and reliable science process skill test for middle and high school students. Multiple‐choice items were generated for each of five objectives. Following pilot testing and revision, the test was administered to middle and high school students in the northeastern United States. The 36‐item test can be completed in a normal class period. Results yielded a mean score of 19.14 and a total test reliability of 0.86. Mean difficulty and discrimination indices were 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
98
0
16

Year Published

1990
1990
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(114 citation statements)
references
References 8 publications
0
98
0
16
Order By: Relevance
“…İlk olarak Burns, Okey ve Wise (1985) BSBT'yi geliştirmişlerdir. Geban, Askar ve Ozkan (1992) tarafından uyarlanmıştır.…”
Section: Bilimsel Süreç Becerileri Testi (Bsbt)unclassified
“…İlk olarak Burns, Okey ve Wise (1985) BSBT'yi geliştirmişlerdir. Geban, Askar ve Ozkan (1992) tarafından uyarlanmıştır.…”
Section: Bilimsel Süreç Becerileri Testi (Bsbt)unclassified
“…As part of this work, there has been an effort to develop assessments to evaluate such skills at both high school (Burns, Okey, & Wise, 1985) and college levels (Brickman, Gormally, Armstrong, & Hallar, 2009). Some studies have suggested that the inquiry approach produces greater achievement in science process skills than the traditional approach (e.g., Gabel, Rubba, & Franz, 1977;Tobin & Capie, 1982;Brickman, Gormally, Armstrong, & Hallar, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the contemporary science education curricula recognize science process skills as important component tools in the construction of scientific knowledge and conceptual change. According to Burns, Okey and Wise (1985), this became more prominent with the advent of several activity and discovery-oriented curricula such as Biological Sciences Curriculum Study (BSCS), Science Curriculum Improvement Study (SCIS), School Science Curriculum Project (SSCP) and Science A Process Approach (SAPA). These curricula emphasized the fact that science is a process in which the learners need to be part of and that if learners are to become scientists, they have to develop these abilities reflective of the behavior of scientists.…”
mentioning
confidence: 99%
“…These curricula also recognized that scientific knowledge had two domains: content knowledge (what scientists have found out) and process skills (what they do to find out). Concepts, explanations, understanding and theories constitute the content of science whereas science process skills refer to the rational and logical thinking skills used in science (Burns, Okey, & Wise, 1985;Necati, 2013;Mutlu & Temiz, 2013). According to Nwosu and Okeke (1995), science process skills are mental and physical abilities and competencies which serve as tools needed for the effective study of science and technology as well as problem solving and individual societal development.…”
mentioning
confidence: 99%